The strategic logic of the contemporary security dilemma - Manwaring, Max G. (SSI monograph., 2011)
The reality and severity of the threats associated with contemporary transnational security problems indicate that the U.S. and its national and international partners need a new paradigm for the conduct of unconventional asymmetric conflict, and an accompanying new paradigm for strategic leader development. The strategic-level basis of these new paradigms is found in the fact that the global community is redefining security in terms of nothing less than a reconceptualization of sovereignty. In the past, sovereignty was the acknowledged and/or real control of territory and the people in it. Now, sovereignty is the responsibility of governments to protect peoples' well-being and prevent great harm to those peoples. Thus, the security dilemma becomes, "Why, when, and how to intervene to protect people and prevent egregious human suffering?" We address some of the strategic-level questions and recommendations that arise out of that debate. We probably generate more questions than answers, but it is time to begin the strategic-level discussion.